Interphase Growth Kinetics and the Partial Electronic Conductivity of Constituents in Sulfide Solid-State Batteries - Alt, Christoph Daniel; Justus Liebig University Giessen (My University, 2025)
Large-scale electrification of transportation and advancements in energy storage are key to achieving net-zero emissions. Solid-state batteries present a promising energy storage solution, expected to enable the use of high-capacity electrode materials such as lithium metal and lithium alloys, while also improving safety. However, effectively integrating high-capacity electrode materials remains a key challenge in unlocking the potential of solid-state batteries. The high reactivity of lithium metal poses both safety and operational challenges, leading to dendrite formation and loss of active redox species (i.e., long-term capacity fading). Since most inorganic solid electrolytes undergo reduction upon contact with alkali metal, the corresponding interphase formation and the resulting long-term increase in cell resistance are often underestimated. However, interphase kinetics and the consequent impact on cell performance strongly depend on the composition and properties of the reaction products. Revealing the interphase composition, growth kinetics, and the influence and role of its individual constitu-ents is crucial for developing protective strategies and enhancing material compatibility. Within this doctoral thesis, the intrinsic transport properties and growth kinetics of the interphase and its constituents for lithiated Li6PS5Cl are investigated, emphasizing their impact on long-term cell operation. Following the quantification of the interphase's partial conductivities through bulk-material synthesis, which revealed a significant resistance contribution over the battery's lifespan, conventional physiochemical concepts were revisited. The Wagner diffusion model, predicting diffusion-controlled interphase growth based on experimental data, was analyzed for solid|solid interfaces alongside the Hebb-Wagner method for accurately quantifying low electronic conductivities in lithium-ion conductors. The former addressed the influence of different interface morphologies on evaluating interphase rate constants by impedance measurements, while the latter revealed the partial electronic conductivity of lithium halides (i.e., LiCl, LiBr, and LiI) present in various interphases. Alloy electrodes, owing to their higher electrode potentials relative to lithium metal, are expected to cause reduced degradation of sulfide solid electrolytes. In this context, In/(InLi)x electrodes – prominent for exhibiting a stable potential of 0.62 V vs. Li+/Li – were first investigated to assess how preparation influences electrode microstructure and performance. Controlling microstructure is critical to avoid current constriction and ensure consistent operation. Studies on thin indium films deposited on current collectors offered insights into interphase growth kinetics at alloying interlayers – an essential challenge for reservoir-free cells – and highlighted the gradual degradation of Li6PS5Cl at the electrode potential of In/(InLi)x. Overall, this doctoral thesis advances the fundamental understanding of intrinsic degradation processes at the electrode|electrolyte interface. In particular, this work provides a new perspective on how multiphase interphases form and evolve over time, depending on their partial ionic and electronic transport properties. It delivers essential insights on previously inaccessible kinetic parameters that now enable more accurate computational simulations, improve the prediction by analytical models, and guide the rational design of more stable materials and interfaces to minimize capacity losses in (reservoir-free) solid-state batteries.
Keywords: Solid-state batteries; solid-state ionics; electrochemistry; ddc:540